A Revision of the Formation Conditions of the Vredefort Crater. Issue 8 (16th August 2022) - Allen, Natalie H.; Nakajima, Miki; Wünnemann, Kai; Helhoski, Søren; Trail, Dustin
Abstract: The Vredefort impact structure, located in South Africa and formed 2.02 Ga, is the largest confirmed remnant impact crater on Earth. The widely accepted impactor diameter and velocity to form this crater are 15 km and 15 km/s, respectively, which produce a crater diameter of 172 km. This is much smaller than the most commonly cited estimates (250–280 km), and while previous results were able to match the geologic evidence known at that time, these impact parameters are not consistent with more recent geological constraints. Here, we conduct impact simulations to model the Vredefort crater formation with the shock physics code impact Simplified Arbitrary Lagrangian Eulerian (iSALE). Our numerical simulations show that combinations of the impactor diameter and impact velocity of 25 km and 15 km/s or 20 km and 25 km/s are able to recreate the larger crater size of ∼250 km. Moreover, these configurations can reproduce shock‐metamorphic features present in the impact structure today, including the distributions of breccia, shatter cones, planar deformation features in quartz and zircon, and melt. Our model also predicts that Vredefort and Karelia, Russia, where an ejecta layer from the impact was found, were approximately 2, 000–2, 500 km apart based on the layer thickness. Additionally, we use this model to predict the potential global effects of such a large impact by estimating the amount of climatically important gases released to the atmosphere at the time. Our work demonstrates the need to revisit previously estimated impactor parameters for large terrestrial craters in order to better characterize impact events on Earth and elsewhere. Plain Language Summary: The Vredefort impact structure, which formed over 2 billion years ago in South Africa, is the largest preserved remnant impact crater on Earth (originally 250–280 km in diameter). It is widely accepted that the crater formed by an impactor 15 km in diameter with velocity 15 km/s, which is based on a numerical simulation that produced a crater size of 172 km. A new model is needed because this model does not reproduce the common estimate of the crater diameter as well as newly identified geologic constraints. Here, we conduct simulations to match these updated constraints. We find that either an impactor with a diameter of 25 km and impact velocity of 15 km/s or a diameter of 20 km and impact velocity of 25 km/s are able to reproduce the crater. We are able to use our results to predict the amount of material ejected by impact at some distance from the crater center. Using this model and an ejecta layer found in Karelia, Russia, we predict that these two locations were 2, 000–2, 500 km apart 2 billion years ago. Such a large impact would have global consequences, especially due to the release of climatically important gases which change the global climate. Key Points: We found an impactor of 20 km with an impact velocity of 25 km/s creates a crater the size of Vredefort Our modeled impactor size and velocity are significantly larger than the previous estimate (15 km, 15 km/s) Our model agrees broadly with the pressure profile seen in the geologic evidence